Predicting thermally induced edge-crack initiation using finite fracture mechanics. (July 2021) - Dölling, S.; Bremm, S.; Kohlstetter, A.; Felger, J.; Becker, W.
Abstract: In temperature-loaded bi-material joints, highly localized stress concentrations occur at the bi-material junction at the free edge. This so-called free-edge effect may cause premature failure in form of an interface crack emanating from the free edge. In the present work, thermal crack initiation is investigated using a coupled stress and energy criterion within the framework of finite fracture mechanics by the example of a uniformly cooled epoxy–glass bi-material specimen. The mechanical analysis is based on the assumption of a plane-strain state, providing a simplified two-dimensional model. Interface stresses and the energy dissipation due to crack initiation are computed efficiently using the scaled boundary finite element method (SBFEM) and the effect of the layer thickness on crack initiation is studied. Dimensional analyses revealed that interface stresses and energy dissipation can be scaled to an arbitrary layer thickness such that only few model evaluations are required. For validation purposes, a finite element reference solution is provided and compared to the results obtained by the SBFEM approach. In addition, a cohesive zone model is applied to validate the predictions of the coupled stress and energy criterion. Highlights: The coupled criterion gives an explanation for thermally induced edge crack initiation. Only physical material parameters are required. Prediction of crack initiation without the need of an inherent flaw. The semi-analytical scaled boundary finite element method is applied. The method of dimensional analysis is used to reduce the computational effort.